Critical role of the NKG2D receptor for NK cell‐mediated control and immune escape of B‐cell lymphoma. Issue 9 (7th July 2015) - Belting, Lena; Hömberg, Nadine; Przewoznik, Margarethe; Brenner, Christoph; Riedel, Tanja; Flatley, Andrew; Polić, Bojan; Busch, Dirk H.; Röcken, Martin; Mocikat, Ralph
<x xml:space="preserve">Abstract</x> Little is known on the control of lymphomas by NK cells. Here, we study the role of the NK group 2D (NKG2D) receptor for the immunosurveillance of lymphoma. By using transplantable tumors as well as a λ‐myc‐transgenic model of endogenously arising lymphoma and NKG2D‐deficient mice, we show that NK cells eliminate tumor cells in vivo after receiving two signals. One step involved the activation of NK cells giving rise to IFN‐γ expression, which was effected by MHCIlow tumor cells or DCs. However, this was necessary but not sufficient to mediate cytotoxicity. Triggering cytotoxicity additionally required a second step, which could be mediated by engagement of the NKG2D receptor. Thus, NKG2D‐deficient NK cells could become activated in vivo, but they were not able to reject transplanted lymphomas or to degranulate in animals bearing autochthonous lymphomas. Tumor growth in NKG2D‐deficient λ‐myc‐transgenic mice was significantly accelerated compared to NKG2D‐competent animals. Whereas the latter developed tumors that lost expression of NKG2D ligands (NKG2D‐L) in late disease stages, this did not occur in NKG2D‐deficient mice. This indicates that NK cells and the NKG2D receptor play a role for control of lymphomas and that selection for NKG2D‐L loss mutants provides a mechanism of tumor escape.